2010
DOI: 10.1002/cncr.25616
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis increases the risk of lung cancer

Abstract: BACKGROUND:The possible effect of pulmonary tuberculosis (TB) on subsequent lung cancer development has been suspected, but the evidence remains inconsistent. The purpose of this study was to perform a nationwide population-based cohort study to investigate the risk of lung cancer after pulmonary TB infection. METHODS: This nationwide population-based cohort study was based on data obtained from the Taiwan National Health Insurance Database. In total, 5657 TB patients and 23,984 controls matched for age and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
144
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 21 publications
5
144
3
3
Order By: Relevance
“…In fact, the most common "root causes" of cancer worldwide are thought to be due to infectious agents, such as in liver (HBV), 57 cervical (HPV), 58 nasopharyngeal (EBV), 59,60 lung (TB), 61 and stomach (H. pylori) 62 cancers. Similarly, chronic inflammatory diseases, such as scleroderma, 63 ulcerative colitis, 64 and Crohn's disease, 65 all predispose to the onset of cancer.…”
Section: 35mentioning
confidence: 99%
“…In fact, the most common "root causes" of cancer worldwide are thought to be due to infectious agents, such as in liver (HBV), 57 cervical (HPV), 58 nasopharyngeal (EBV), 59,60 lung (TB), 61 and stomach (H. pylori) 62 cancers. Similarly, chronic inflammatory diseases, such as scleroderma, 63 ulcerative colitis, 64 and Crohn's disease, 65 all predispose to the onset of cancer.…”
Section: 35mentioning
confidence: 99%
“…It is well known that there is a significant relationship between the history of pulmonary TB and the risk of LC (5,16). It has also been reported that there is a synergistic interaction with the daily amount and duration of smoking and the history of pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…4 The simultaneous or sequential occurrence of pulmonary tuberculosis and Lung carcinoma in the same patient has been reported in various case series and case-control studies. (5)(6)(7)(8)(9)(10) It has been suggested that inflammation and pulmonary fibrosis caused by tuberculosis can induce genetic damage, which can increase lung carcinoma risk. (11)(12)(13) The increased occurrence of Lung carcinoma in patients with tuberculosis can also be related to infection-induced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%